2021
DOI: 10.1371/journal.pone.0259302
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of toxigenic fungi and mycotoxins in Arabic coffee (Coffea arabica): Protective role of traditional coffee roasting, brewing and bacterial volatiles

Abstract: Fungal infection and synthesis of mycotoxins in coffee leads to significant economic losses. This study aimed to investigate the prevalence of toxigenic fungi, their metabolites, and the effect of traditional roasting and brewing on ochratoxin A (OTA) and aflatoxins (AFs) contents of naturally contaminated coffee samples. In addition, in vivo biocontrol assays were performed to explore the antagonistic activities of Bacillus simplex 350–3 (BS350-3) on the growth and mycotoxins synthesis of Aspergillus ochraceu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 36 publications
1
2
0
Order By: Relevance
“…At days 3, 5 and 7, the colony size of fungi exposed to yeast VOCs were 25.54 ± 4.32 mm, 28.60 ± 3.2 mm and 29.80 ± 2.5 mm compared to 34.50 ± 1.3 mm, 35.0 mm ± 1.9 and 36.0 ± 2.0 mm for the control, respectively. In compliance with the present study, B. simplex volatiles, composed mainly of quinoline and benzenemethanamine, significantly inhibited A. flavus and A. carbonarius in coffee beans [43]. These findings suggest potential application of Cyberlindnera jadinii 273 during storage of food items in commercial as well as domestic settings.…”
Section: Effects Of Cyberlindnera Jadinii 273 Volatiles On Fungal Growthsupporting
confidence: 89%
“…At days 3, 5 and 7, the colony size of fungi exposed to yeast VOCs were 25.54 ± 4.32 mm, 28.60 ± 3.2 mm and 29.80 ± 2.5 mm compared to 34.50 ± 1.3 mm, 35.0 mm ± 1.9 and 36.0 ± 2.0 mm for the control, respectively. In compliance with the present study, B. simplex volatiles, composed mainly of quinoline and benzenemethanamine, significantly inhibited A. flavus and A. carbonarius in coffee beans [43]. These findings suggest potential application of Cyberlindnera jadinii 273 during storage of food items in commercial as well as domestic settings.…”
Section: Effects Of Cyberlindnera Jadinii 273 Volatiles On Fungal Growthsupporting
confidence: 89%
“…Several studies have previously reported both microbial [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ] and mycotoxin contamination [ 25 , 27 , 30 , 31 , 32 , 33 ] in coffee grains. The later are essentially ochratoxin A, the only mycotoxin monitored so far in coffee production (green and roasted coffee) [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The best combination was defined at a high roast scheme with traditional brewing, and the cumulative reduction rates were 62.38% for AFs and 64.7% for OTA. It is worth noting that roasting temperatures applied to coffee beans in Arab countries are lower than those applied in other countries to preserve the traditional organoleptic characteristics such as color and flavor [ 125 ].…”
Section: Subsequent Detoxification Treatments Used In Solid Foods And...mentioning
confidence: 99%